The Influence of Achievement in the Character Habituation Program on Students' Grades at Makarios Junior High School, West Jakarta, during the 2023/2024 Academic Year - Mauriths, Rolland (Jurnal Pendidikan Makarios, 2024)
This research investigates the impact of the Character Habituation program on student academic performance at Makarios Christian School at Junior High level during the 2023/2024 academic year. Character education has emerged as a critical element in the development of students' ethical principles, conduct, and educational achievement. This investigation utilized a comparative analytical framework to evaluate the influence of character habituation approach on individual student performance and the broader academic milieu, using Bandura’s (1977) Social Learning Theory and Pearson’s (1901) theory of Correlation analysis. The findings indicate that: 1) The investigation revealed that students who regularly engaged in the Character Habituation program generally attained superior academic grades. This observation implies a moderate positive effect of the program on student performance. 2) Students who engaged in the program continued to encounter academic obstacles, whereas a select few who abstained from participation still achieved elevated grades. This suggests that additional variables, such as individual academic capabilities or learning difficulties, also play a significant role in influencing academic outcomes. 3) The outcomes from the Pearson correlation study suggested a moderate positive connection (r = 0.45) tying program involvement to educational achievement, illustrating that although the program aids in academic results, it is not the only major contributor. The implications of these findings are anticipated to inform educational policy by emphasizing the significance of character habituation programs in promoting comprehensive student development, proposing that the incorporation of moral and social principles into the educational curriculum can enhance both academic results and enduring values.